Platelet activation through CD62P and the formation of platelet–monocyte complexes are associated with the exacerbation of mucosal inflammation in patients with ulcerative colitis - Yasuki Sano; Takashi Tomiyama; Naoto Yagi; Yuka Ito; Yusuke Honzawa; Tomomitsu Tahara; Tsukasa Ikeura; Toshiro Fukui; Shinji Shimoda; Makoto Naganuma (Scientific Reports)
Abstract Ulcerative colitis (UC) is a refractory, chronic inflammatory bowel disease of unknown etiology. Although platelets are activated in UC, their relevance in pathophysiology remains unclear. We analyzed the correlation of platelet activation and platelet–monocyte complexes (PMCs) with severity of mucosal inflammation using the Mayo endoscopic subscore (MES). Platelet activation marker, CD62P was upregulated in patients with UC compared with that in healthy controls (P < 0.05). CD62P expression was significantly higher in patients with MES3 (severe inflammation) than in those with MES ≤ 2 (endoscopic remission to moderate inflammation) (P < 0.001). The concentration of sCD62P in patients with MES0 (endoscopic remission) was significantly higher than in those with MES ≥ 1 (P < 0.01). The expression of CD40L, CD63, PAC-1, annexin V, and CD36, and the concentrations of sCD40L, PF4, and RANTES did not correlate with MES. The proportion of PMCs in patients with MES3 was higher than in those with MES ≤ 2 (P < 0.05). CD16 expression on monocytes with platelets was significantly higher than in monocytes without platelets (P < 0.001). Patients with complete remission after treatment showed significant reduction in PMCs 3 months after treatment (P < 0.05) but had no change in CD62P and sCD62P. Our data suggest that platelet activation via the CD62P–PMC axis is involved in UC pathophysiology.